Movement Analysis of DIMAS SAPUTRA Smash with Kinovea in the West Kalimantan Regional KAPOLDA CUP I Volleyball Final - Muhammad Suhairi; Ade Rahmat; Rajidin; Syaparudin; Yuyun Rusmita (Indonesian Journal of Physical Education and Sport Science)
Study purpose. Biomechanics is a branch of science that studies the forms and types of human movement based on mechanical principles in a sport that can minimize the occurrence of sports injuries. The purpose of this study was to see the effectiveness of Dimas Saputra's smash open movement at the 2023 West Kalimantan Regional Police Chief Championship.